Effect of Blood Flow Restriction Training on Cardiorespiratory Endurance, Quality of Life, and Muscle Strength among Postmenopausal Women: A Research Protocol for a Randomised Clinical Trial - Kashish Maggu; Mandeep Kumar Jangra; Akanksha Saxena (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Postmenopause is a physiological phase that occurs after 45-55 years of age, associated with musculoskeletal, cardiovascular, metabolic and functional changes. Blood Flow Restriction Training (BFRT) is an emerging low-intensity exercise technique that can yield gains in strength and endurance comparable to high-load Resistance Training (RT). Need of the study: Menopause-related hormonal changes contribute to reduced muscle strength, decline in cardiorespiratory endurance, and impaired Quality of Life (QoL). BFRT has shown positive effects on muscular outcomes; however, evidence regarding its impact on cardiorespiratory endurance and QoL in postmenopausal women remains limited. Aim: To investigate the effect of BFRT on cardiorespiratory endurance, QoL and muscle strength among postmenopausal women. Materials and Methods: A randomised clinical trial will be conducted at Maharishi Markandeshwar Institute of Physiotherapy and Rehabilitation, Maharishi Markandeshwar (Deemed to), Mullana-Ambala, Haryana, India, from May 2026 to March 2027. A total of 70 postmenopausal women aged 45-55 years, will be allocated to the experimental group and control group. The experimental group will receive BFRT with elastic band exercises. In contrast, the control group will receive resistance exercises through an elastic band three times a week for four weeks. Outcomes, including cardiorespiratory endurance, QoL, and muscle strength, will be assessed using the Queen’s College step test, a Handheld Dynamometer (HHD), the 5-times sit-to-stand test, and the Menopause-Specific Quality of Life (MENQOL) Questionnaire at baseline and after the intervention period. Shapiro-Wilk test, Parametric tests (paired and independent t-tests) and non parametric tests (Wilcoxon Signed-Rank and MannWhitney) will be applied. The p-value